2014
DOI: 10.4028/www.scientific.net/amr.1004-1005.1523
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Aspects of Durable Geocement Matrix Formation - Role of Alkali

Abstract: Less than half a century ago just an idea of presence of free alkalis in a ceramic matrix was considered by ordinary Portland cement people as an absurd one and this was a basic postulate accepted in chemistry of cements. In 1957 a scientist from Ukraine (USSR) Viktor Glukhovsky put forward an assumption which was taken as a base for development and bringing into practice of construction a principally new class of cementitious materials which first appeared in the field under a name of alkaline (now also known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…-the quality of the binder, which is characterized by viscosity, surface tension, the presence of gels and microgels, particle size, colloidal stability and adhesion strength. The consistency of the binder itself and the strength, hardness and durability of materials based on it depend on the type and composition of these indicators [1][2][3][4][5][6][7][8][9][10][11][12]; -dependence of the surface tension of uncured mineral binders on the nature of the solvent. With an increase in the concentration of solvents, the surface tension of unconfined binders decreases, and the greater, the less the surface tension of the solvents [25][26][27].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…-the quality of the binder, which is characterized by viscosity, surface tension, the presence of gels and microgels, particle size, colloidal stability and adhesion strength. The consistency of the binder itself and the strength, hardness and durability of materials based on it depend on the type and composition of these indicators [1][2][3][4][5][6][7][8][9][10][11][12]; -dependence of the surface tension of uncured mineral binders on the nature of the solvent. With an increase in the concentration of solvents, the surface tension of unconfined binders decreases, and the greater, the less the surface tension of the solvents [25][26][27].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…In general, the main properties of the binders themselves are considered: the processes of structure formation, strength, frost resistance, etc. [1][2][3][4][5][6][7][8][9][10][11][12]. Occasionally, publications aimed at studying special properties (heat resistance, fire resistance, corrosion resistance, etc.)…”
Section: Introducitonmentioning
confidence: 99%
“…There are many publications devoted to the problems of alkaline activation of metakaolin, a mixture of metakaolin with ash in the presence of solutions of alkalis in which the action of alkaline ions is noted not only in the stage of metakaolin destruction, but also in the final stage of the formation of the condensed structure [1]. In [2][3][4][5][6] shows data on the interaction of mixtures of kaolin and feldspar, activated liquid glass, and it is shown that polycondensation is a three-step process: dissolving kaolin and feldspars to form a gel, condensing the gel and polycondensation it into three-dimensional structures Al and Si, in which Na + or K + compensate for the electric charge of aluminum. In the course of polycondensation, water acts as a solvent and as a reaction agent.…”
Section: Introductionmentioning
confidence: 99%